Effectiveness of self-etching primer versus conventional etch and bond technique in fixed orthodontic treatment - Noor Sam .A,; Asma .A.A.A, (Universiti Kebangsaan Malaysia, 2012)
A good adhesive is an important factor to consider in orthodontic bonding. Frequent bracket failure prolongs treatment duration and causes inconvenience to patient and operator. This study aimed to compare the effectiveness of two bonding agents, i.e. the self etching primer (SEP) and the conventional etch and bond (CEB) by monitoring the incidence, time and sites of bracket failure. Eighty orthodontic patients were recruited after informed consent were obtained. A randomized split mouth technique was used where one side was bonded with CEB agent, while the other side was bonded using SEP agent. All bonded brackets were examined every 4 weeks for 20 months. Incidence of bracket failure was noted and comparison between the two groups was done using paired t-test. Time and frequent site of failure were also assessed. Out of 1314 brackets, only 33 brackets were debonded with 16 from SEP group and 17 from CEB group which statistically insignificant (p>0.05). Almost 55% of bracket failure occurred during the first 3 months after bonding for both adhesives with lower premolars was most the frequent site to fail in both adhesives (39.4%). Bracket bonded on the left side failed significantly compared to the right side. In conclusion, both self-etching primer and conventional acid-etch bonding agents are equally effective in retaining brackets clinically. Bracket failure mostly occurres during the first 3 months after bonding. The premolar brackets and the left side are mostly debonded when compared to other sites.